International Conference on Artificial Intelligence for Smart Community AISC 2020, 17-18 December, Universiti Teknologi Petronas, Malaysia - Ibrahim, Rosdiazli; K. Porkumaran; Kannan, Ramani; Mohd Nor, Nursyarizal; S. Prabakar (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This conference proceeding gather a selection of peer-reviewed papers presented at the 1st International Conference on Artificial Intelligence for Smart Community (AISC 2020), held as a virtual conference on 17-18 December 2020, with the theme Re-imagining Artificial Intelligence (AI) for Smart Community to apply computational intelligence for biomedical instruments, automation & control, and smart community to develop suitable solution for various real-world application. The conference virtually brought together researchers, scientists, engineers, industrial professionals, and students presenting important results in the related field of healthcare technology, soft computing technologies, IoT, evolutionary computations, automation and control, smart manufacturing and smart cities. Researchers and scientist working in the allied domain of Artificial Intelligence and others will find the book useful as it will contain some latest computational intelligence methodologies and applications.
1. Design of PID Controller for Integrating Processes with Inverse Response -- 2. Environmental Feasibility Survey of Solar Photovoltaic Cells -- 3. Intelligent Control Techniques For Parameter Tuning Of Pid Controller For Lfc With Emphasis On Genetic Algorithm -- 4. Simplified Decoupler Based Fractional Order PID Controller for Two Variable Fractional Order Processess -- 5. Improved Centralized Pid Controller With Disturbance Rejection For Lti Multivariable Processes -- 6. Tuning of P+I+D Controller Using SIMC Method for Processes with Time Delay and RHP Poles -- 7. Independent Controller Design For Non- Minimum Phase Two Variable Process With Time Delay -- 8. Control Of Dc Link Voltage And Load Voltage Variations In A Pitch Angle Controlled Pmsg Based Wind Energy Conversion System -- 9. A Novel Approach of Wind MPPT Using Fuzzy Logic -- 10. Shale Gas Productive Volume Optimization.
Keywords: Computational intelligence; Artificial intelligence; Quantitative research; Computational Intelligence; Artificial Intelligence; Data Analysis and Big Data